2008
DOI: 10.1158/0008-5472.can-07-2973
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Expression of a Ligand for the NKG2D Receptor by Proteasome Inhibitors

Abstract: The interaction of the activating receptor NKG2D with its ligands plays an important role in immunosurveillance of tumors and infectious pathogens, but dysregulation of this system may lead to autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 49 publications
(60 reference statements)
7
73
0
Order By: Relevance
“…In addition, it has been reported that proteasome inhibitor treatment leads to a higher sensitivity to NK-cell-mediated killing by upregulation of ULBP2 expression [22], supporting its potential relevance in the development of anticancer therapy. We next evaluate whether NKG2D/ULBP2 interaction exerted similar effects than NKG2D cross-linking and found that activation of NKG2D receptor with platebound ULBP2 efficiently inhibited NK-cell migration (*p < 0.05; Fig.…”
Section: Nkg2d and Nkg2a Ligation Rescues Impaired Migrationmentioning
confidence: 90%
“…In addition, it has been reported that proteasome inhibitor treatment leads to a higher sensitivity to NK-cell-mediated killing by upregulation of ULBP2 expression [22], supporting its potential relevance in the development of anticancer therapy. We next evaluate whether NKG2D/ULBP2 interaction exerted similar effects than NKG2D cross-linking and found that activation of NKG2D receptor with platebound ULBP2 efficiently inhibited NK-cell migration (*p < 0.05; Fig.…”
Section: Nkg2d and Nkg2a Ligation Rescues Impaired Migrationmentioning
confidence: 90%
“…Next we focused on posttranslational pathways important for NKG2D ligand regulation. It has been recognized that proteasomal inhibition is important for the regulation of NKG2D ligands, specifically for the induction of cell surface-expressed ULBP2 (17). Hence, we hypothesized that the different expression patterns of CH 3 SeH and FR901228 could be a result of differences in proteasome regulation.…”
Section: The Nkg2d Ligand-regulating Effect Of Ch 3 Seh and An Hdac Imentioning
confidence: 97%
“…All ligands are MHC class I-related glycoproteins (6). Different forms of cellular stress result in increased NKG2D ligand surface expression, including heat shock, virus infection, inflammatory cytokines, histone deacetylase (HDAC) inhibitors, propionic acid, retinoic acid, proteasome inhibitors, Toll-like receptor (TLR) signaling, and DNA damage response (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Moreover, surface expression of NKG2D ligands on a variety of tumors derived from different origins present an attractive target for anticancer therapy (18 -20).…”
mentioning
confidence: 99%
“…6 Recruitment to detergent-resistant membranes is a mechanism described for incorporation of proteins into exosomes (40); thus, why would ULBP3 but not ULBP2 be preferentially included into exosomes? We hypothesized that ULBP2 is not excluded from exosomes but rather is more susceptible to metalloprotease attack and is therefore lost by proteolysis before inclusion into exosomes.…”
Section: Differential Kinetics and Shedding Of Ulbp1 -2 And -3-tomentioning
confidence: 99%
“…In general, NKG2D-L are not expressed ubiquitously; instead, they are expressed in response to several types of cellular stress, such as pathogen infection (4), DNA damage (5), proteasome inhibition (6), and tumor transformation (7). For example, MICA/B are expressed in epithelial tumors, melanoma, neuroblastoma, various hematopoietic malignancies, and carcinomas; ULBPs are found in leukemia, gliomas and melanomas.…”
mentioning
confidence: 99%